African Land Reform Under Economic Liberalisation 2021
DOI: 10.1007/978-981-16-4725-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Land Administration, Chiefs, and Governance in Ghana

Abstract: This chapter examines the role of chiefs in the administration of land in Ghana within a historical framework dating back to the pre-colonial period. It examines the relationship between the dynamic of internal political factors and of international pressures for governance reforms. It argues that while present land governance reforms fit into the framework of market liberal governance reforms advocated by international financial institutions and the USA, the origins of the present role of chiefs in land admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…He is said to be the descendant of the rst settler on the land and by custom has right of ownership over the land (Okyere&Bedu, 2022; Akolgo-Azupogo, Bardy & Rubens, 2021; Bugri & Yuonayel, 2015; Yaro, 2012; Kasanga and Kotey (2001). Tribal chiefs, because of their social and political status and the recognition which they receive from the public from long before the colonial era, also have authority on land, but this is limited (Amanor, 2022;Lund, 2008).…”
Section: Land Tenure and Governance In The Bolgatanga Municipalitymentioning
confidence: 99%
“…He is said to be the descendant of the rst settler on the land and by custom has right of ownership over the land (Okyere&Bedu, 2022; Akolgo-Azupogo, Bardy & Rubens, 2021; Bugri & Yuonayel, 2015; Yaro, 2012; Kasanga and Kotey (2001). Tribal chiefs, because of their social and political status and the recognition which they receive from the public from long before the colonial era, also have authority on land, but this is limited (Amanor, 2022;Lund, 2008).…”
Section: Land Tenure and Governance In The Bolgatanga Municipalitymentioning
confidence: 99%
“…In fact, in Ghana, tensions and conflicts become prevalent when land is misappropriated or commoditised with emphasis on its market value and not its intrinsic cultural and social value. As far as the idea of the customary is concerned, Amanor (1999) and Berry (2001) have argued that, the notion of the 'customary' was structured around reinventions of African traditions by colonial officials and so full of ambiguities and prejudices. For example, Berry contends that the effort of colonialists to redefine the notion of 'customary' in favour of colonial interests rather produced negative outcomes in which chiefs, elders and colonial officials colluded to deprive the peasantry and the youth of heritable land.…”
Section: Introductionmentioning
confidence: 99%
“…Structural divisions among smallholders have been noted, however in terms of differences in sociocultural and economic factors. Empirically, Amanor (1999) observed that structural inequities based on gender, ethnicity and age are often deepened in the context of commercialisation. Bernstein (2010) and Oya (2007) argue that the process of smallholder commercialisation has two major implications: the creation of entrepreneurial smallholders (petty commodity producers) and the increase of social differentiation.…”
Section: Introductionmentioning
confidence: 99%